Araucania-Norpatagonia III Tensiones y reflexiones en un territorio en construcción permanente - Azcoitía, Alfredo; Nicoletti, María Andrea; Lanza, Mariano (Aperturas, 2021)
This third volume of Argentine-Chilean binational studies continues and deepens the inquiries about the construction of social meanings in the territory called Araucanía-Norpatagonia. Again, the starting point is the plurality of a territory of diffuse and artificial limits, a plurality that is evidenced in the dialogue, the different perspectives of approach, the polysemy and the tensions behind concepts and representations observed through a particular epistemological gaze and necessary for a territory of late integration such as that of the Chilean-Argentine Patagonia. In this case, the book is organized in three axes. The first, "Disputed territorial constructions", includes works that analyze, from different disciplinary points of view, the tensions that run through the production of meanings about the territory. The second is "Neoliberalism and commodification of nature" and brings together studies that focus on the different forms and open scenarios of dispute for the appropriation of land, water and biodiversity within the framework of the historical cycle that began with the conservative reaction of the late 1970s. Finally, the third axis "New approaches to thinking about a binational territory" contains articles that, also from different perspectives and problems, share the concern to carry out conceptual and methodological reflections to contribute to drawing future studies from a binational perspective.